2017
DOI: 10.5851/kosfa.2017.37.4.518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 27.12 MHz Radio Frequency on the Rapid and Uniform Tempering of Cylindrical Frozen Pork Loin (Longissimus thoracis et lumborum)

Abstract: Quality characteristics of frozen cylindrical pork loin were evaluated following different tempering methods: 27.12 MHz curved-electrode radio frequency (RF) at 1000 and 1500 W, and forced-air convection (FC) or water immersion (WI) at 4°C and 20°C. The developed RF tempering system with the newly designed curved-electrode achieved relatively uniform tempering compared to a parallel-plate RF system. FC tempering at 4°C was the most time-consuming process, whereas 1500 W RF was the shortest. Pork sample drip lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…these results are consistent with those reported by Choi, Park, Yang, et al (2017). Less structural damage corresponded to larger muscle cell areas and smaller intracellular space areas in FM samples, and severe tissue damage resulted in the thawed meat having decreased water-holding capacity (Li et al, 2020).…”
Section: Histological Observation and Sds-page Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…these results are consistent with those reported by Choi, Park, Yang, et al (2017). Less structural damage corresponded to larger muscle cell areas and smaller intracellular space areas in FM samples, and severe tissue damage resulted in the thawed meat having decreased water-holding capacity (Li et al, 2020).…”
Section: Histological Observation and Sds-page Analysissupporting
confidence: 92%
“…After thawing, the muscle cell damage due to the formation of ice crystals resulted in increased cavities between muscle fibers. Choi, Park, Yang, et al (2017) reported that the formation of intracellular and extracellular ice crystals during freezing and thawing processes caused tissue damage, thereby resulting in high drip and thawing losses (Choi, Park, Yang, et al, 2017;Kaewkot et al, 2022). The RFWI and RFAC samples had significantly larger muscle cell areas than those of the WI and AC samples (Figure 3).…”
Section: Histological Observation and Sds-page Analysismentioning
confidence: 98%
“…The principle aim of the meat industry is to produce safe products while improving sensory, texture, and quality properties and ensuring oxidative stability (Dominguez-Hernandez et al, 2018). The effects of freezing, which increases shelf life by preventing oxidative degradation, on product quality has been extensively studied (Choi et al., 2017; Leygonie et al, 2012a; Soyer et al, 2010). Tenderness and juiciness, which comprise crucial properties for consumers, exhibit more positive results upon freezing/thawing rather than chilling meat (Lagerstedt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The methods given by Choi et al [8] was used to calculate cooking loss. The thawed sample (50 g) was placed in a polyethylene bag and cooked for 25 min at 80°C in a water bath (GFL 1052, Germany) until it reached 75°C.…”
Section: Cook Lossmentioning
confidence: 99%
“…Many factors, including the thawing process, can affect meat quality [7]. Several studies have examined the effects of different thawing methods on changes in meat quality, such as water retention, tenderness, color, and flavor [15,16,42]; lipid oxidation [22], and microbial growth [8], but there is little information on the microstructural effects of different thawing techniques on histomorphological techniques. Official standards do not provide information on the assessment of the thawing process and its impact on food.…”
Section: Introductionmentioning
confidence: 99%